E-story and writing skill among second language learners - Abd Rahim, Normaliza; Abdul Halim, Hazlina; Mansor, Nor Shahila (Sakarya University, 2017)
The study focused on the use of e-story and writing skill among the second language Korean learners. The objectives of the study were to identify and discuss the students’ writing in the second language by using e-story. The samples of the study involved all 21 participants from two classes of Malay language at one of the universities in South Korea. The participants were taught in the Malay language as the second language for two hours a week in fourteen weeks. The participants were to rewrite the e-story learnt. The result of the study revealed that majority of the participants managed to rewrite the e-story. The participants also seemed to be interested in the e-story since it is different than the normal classroom. Also, the results showed that e-story manage to enhance study learning in the second language. It is hoped that further study will focus on other e-story from the Malay folklore to enhance second language learners in learning.